One‐ and Two‐dimensional High‐performance Thin‐layer Chromatography as an Alternative Analytical Tool for Investigating Polyphenol–Protein Interactions. Issue 5 (23rd July 2013) - Tscherch, Kathrin; Biller, Julia; Lehmann, Mareen; Trusch, Maria; Rohn, Sascha
ABSTRACT: Introduction: Polyphenols and simple phenolic compounds are able to react with other food constituents during processing and storage. In the past, it has been shown that their reaction with proteins can lead to changes of the technofunctional or even physiological properties of both compound classes. However, identification of specific binding sites of small molecules within a protein sequence (and the corresponding conformational position) is still challenging. Objective: Investigating the reaction between different food proteins and phenolic compounds in alkaline medium with one‐ and two‐dimensional high‐performance thin‐layer chromatography (HPTLC) coupled to matrix‐assisted laser desorption/ionisation (MALDI) with time‐of‐flight (TOF) MS for analysing the peptide profiles after tryptic digestion. Methods: After modification with phenolic compounds, protein derivatives were digested and peptides were separated with one‐ and two‐dimensional HPTLC. Peptide profiles were detected with visible and UV wavelengths as well as with fluorescamine, ninhydrin and 2, 2′‐azino‐ bis (3‐ethylbenzothiazoline‐6‐sulphonic acid staining. In order to perform mass spectrometric measurements, peptides separated in the first dimension were analysed by MALDI/TOF/MS. Results: Results show that the phenolic acids applied in this study show different specificity and susceptibility when modifying proteins resulting in changes of the peptide profiles, peptide quantity, polarity, UV‐activity, radical‐scavenging activity and molecular mass. Conclusion: One‐ and two‐dimensional HPTLC supported by mass spectrometric detection represents an innovative, alternative tool for investigating and understanding polyphenol–protein interactions. This approach enables the identification of binding sites inside the protein chain and contributes to understanding the mechanism of polyphenol–protein interactions in vitro and in vivo . Copyright © 2013 John Wiley & Sons, Ltd. Abstract : In this study, one‐ and two‐dimensional HPTLC supported by MALDI/TOF/MS detection was successfully applied for the investigation of tryptically digested protein–phenol derivatives. Moreover, this technique enabled investigating the influence of selected phenolic compounds on the proteins and corresponding peptides in terms of quantity, polarity, UV activity, radical‐scavenging activity and mass. This approach enables the identification of binding sites inside the protein chain and contributes to understanding the mechanism of polyphenol–protein interactions in vitro and in vivo .